Optimization of the Quality of Administrative Services at the Population and Civil Registration Office of Takalar Regency (Pinisi Journal of Officers Review, 2024)
Optimizing the quality of administrative services at the Takalar Regency Population and Civil Registration Office based on factors that support and hinder services that can be seen from the community's response. The method in this research is descriptive research. This study aims to determine the optimization of the quality of administrative services at the Takalar Regency Population and Civil Registration Office. Data collection techniques with observation, interview, and documentation techniques. Data analysis techniques with data collection, data presentation, data condensation and conclusion drawn. The results of this study show that the quality of public services at the Takalar Regency Population and Civil Registration Office which is assessed from five dimensions, namely, Tangibles, Reliability, Responsiviness, Assurance, and Emphaty has been running in accordance with the expectations of the community, as well as in accordance with the Standard Operating Procedure (SOP) in the service process. The condition of service facilities and infrastructure is quite adequate with a number of employees of 30 people which is a supporting factor in providing services and each employee is required to take part in training so that it adds insight into public services at the Takalar Regency Population and Civil Registration Office office has been running well.